1960
DOI: 10.1039/jr9600004369
|View full text |Cite
|
Sign up to set email alerts
|

848. The infrared spectra of cobalt(III) ethylenediamine complexes. Part I. Vibrations of the ethylenediamine chelate ring

Abstract: Baldwin. 4369 848. The Infrared 8pectra of Cobalt(Ir1) Ethylenediarnine Complexes. Part I . Vibrations of the Ethylenediamine Chelate Ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1964
1964
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…The corresponding bands in the N-deuterated complexes appeared a t about 1 180-1 170 cm-l, in agreement with published data for other ethylenediamine metal complexes (6,7).…”
supporting
confidence: 79%
“…The corresponding bands in the N-deuterated complexes appeared a t about 1 180-1 170 cm-l, in agreement with published data for other ethylenediamine metal complexes (6,7).…”
supporting
confidence: 79%
“…For the assignment of geometrical configuration to these complexes, infrared spectroscopy was used. Various workers have employed [31][32][33][34][35][36] the NH 2 deformation mode in the 1700-1500 cm )1 region, CH 2 rocking mode in the 900-850 cm )1 and M-N stretching mode in the 610-500 cm )1 region to distinguish between the cis-and trans-isomers of chromium(III)-ethylenediamine complexes. Baldwin [34] suggested that the most consistent variations between the spectra of cisand trans-isomers were found in the CH 2 rocking region (900-850 cm )1 ).…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%
“…Several attempts have been made to relate differences in the infrared spectra to the geometrical configuration structure of the complexes [31][32][33][34][35][36]. For the assignment of geometrical configuration to these complexes, infrared spectroscopy was used.…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%
“…absorption bands of the two compounds together with tentative assignnients of the various bands are given in Table 3. Given that both compounds A and C are cyanoamminebis(ethylenediamine)cobalt(III) salts, a comparison of the spectra of the two compounds in the 1580-1620, 870-900 and 610-500 cm-' regions would lead to the prediction that compound A had the cis-configuration and compound C had the trans-configuration (15)(16)(17).…”
Section: T L~t R L L~~l E~~i~mentioning
confidence: 99%